2004
DOI: 10.1242/jeb.01225
|View full text |Cite
|
Sign up to set email alerts
|

Acclimatization to 4100 m does not change capillary density or mRNA expression of potential angiogenesis regulatory factors in human skeletal muscle

Abstract: Increased skeletal muscle capillary density would be a logical adaptive mechanism to chronic hypoxic exposure. However, animal studies have yielded conflicting results, and human studies are sparse. Neoformation of capillaries is dependent on endothelial growth factors such as vascular endothelial growth factor (VEGF), a known target gene for hypoxia inducible factor 1 (HIF-1). We hypothesised that prolonged exposure to high altitude increases muscle capillary density and that this can be explained by an enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 49 publications
3
55
3
Order By: Relevance
“…3) (Dempsey et al, 2006). Finally, Lundby et al (2004) have demonstrated no increase in the expression of either hypoxia inducible factor 1a or vascular endothelial growth factor mRNA in muscle after 2 week at a similar altitude to our investigation, and no increase in capillary-to-muscle fibre ratio after 8 week.…”
Section: Decreased Critical Powersupporting
confidence: 68%
“…3) (Dempsey et al, 2006). Finally, Lundby et al (2004) have demonstrated no increase in the expression of either hypoxia inducible factor 1a or vascular endothelial growth factor mRNA in muscle after 2 week at a similar altitude to our investigation, and no increase in capillary-to-muscle fibre ratio after 8 week.…”
Section: Decreased Critical Powersupporting
confidence: 68%
“…In contrast, it has also been reported that systemic hypoxia does not cause changes in the capillary bed in rodents (11% O 2 for 2 weeks and 13% O 2 for 5 months) [46, 47]. In humans exposed to 4,100 m altitude (corresponding to approximately 13% O 2 ) for 2 and 8 weeks, there were no change in VEGF levels and no evidence of angiogenesis [48]. The oxygen saturation in humans during exposure to 14% O 2 will only cause a decrease from 95 to 89% of oxygen saturation [49].…”
Section: Discussionmentioning
confidence: 99%
“…However, peak exercise leg O 2 extraction in the natives was 7 percentage units lower than in the lowlanders, despite the fact that Vo 2max in normoxia was comparable between both groups. The only structural difference that could explain this reduced O 2 extraction capacity in the altitude natives was that they had less capillaries per muscle fiber than the lowlanders (Lundby et al, 2004b;Lundby et al, 2006).…”
Section: Calbet and Lundbymentioning
confidence: 98%